Instrumentation And Interpretation ? Introduction - H. Mori (Deep Foundations Institute, 1991)
The session chairman, Dr. H. Mori, welcomed the delegates to Discussion Session 8. AUTHORS PRESENTATIONS 1 . G. Price, Building Research Establishment. UK Mr. Price expanded on the content of his paper and presented elements of various case histories of bored piles instrumented by the Building Research Establishment. In particular, the interpretation of data from instrumented piles is critically related to: (i) the construction process (ii) concrete stiffness and variability (iii) the effects on the pile due to installing instruments The main role of the instrumentation in the examples presented was to establish pile performance under service loading conditions. Of particular interest is the mobilisation of skin friction and soil shear modulus.